Flow Mediated Dilatation Is Reduced with the Progressive Stages of Glomerular Filtration Rate and Albuminuria in Type 2 Diabetic Patients without Coronary Heart Disease - Hiroyuki Ito; Mina Nakashima; Kentaro Meguro; Haruki Furukawa; Hitomi Yamashita; Akifusa Takaki; Chizuko Yukawa; Takashi Omoto; Masahiro Shinozaki; Shinya Nishio; Mariko Abe; Shinichi Antoku; et al. (Journal of Diabetes Research)
We aimed to clarify the usefulness of measuring the flow mediated dilatation (FMD) in patients with type 2 diabetes mellitus without and with coronary heart disease (CHD). The FMD was measured in 480 patients with type 2 diabetes and in 240 nondiabetic subjects. The FMD was significantly lower in the subjects with CHD (n = 145, 5.4±3.2%) than in those without CHD (n = 95, 6.9±3.5%) among the nondiabetic subjects. The FMD was also lower in the subjects both with CHD (n = 161, 5.6±2.8%) and without CHD (n = 319, 6.1±3.3%) among the patients with diabetes compared to those without both diabetes and CHD. The FMD showed a significant positive correlation with the estimated glomerular filtration rate (eGFR) in the diabetic patients without CHD, while there was no significant association in those with CHD. The FMD was significantly lower with the progressive stages of the GFR or albuminuria in the patients without CHD among those with diabetes, although the FMD was not different in those with CHD. In conclusion, the FMD is considered to be useful for the detection of atherosclerosis in patients with type 2 diabetes, even if overt macroangiopathy is not diagnosed.